Sowing the wind and reaping the whirlwind? The effect of wind turbines on residential well-being - Christian Krekel; Alexander Zerrahn (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
We investigate the effect of the physical presence of wind turbines on residential well-being in Germany, using panel data from the German Socio-Economic Panel (SOEP) and a unique novel panel data set on more than 20,000 wind turbines for the time period between 2000 and 2012. Using a Geographical Information System (GIS), we calculate the proximity between households and the nearest wind turbine as the most important determinant of their disamenities, e.g. visual interference into landscape aesthetics. Our unique novel panel data set on wind turbines, which was collected at the regional level, includes their exact geographical coordinates and construction dates. This allows estimating the causal effect of the physical presence of wind turbines on residential well-being, using a difference-in-differences design. To ensure comparability of the treatment and control group, we apply propensity-score and novel spatial matching techniques based on exogenous weather data and geographical locations of residence, respectively. We show that the construction of a wind turbine within a treatment radius of 4,000 metres around households has a significantly negative effect on life satisfaction. For larger treatment radii, no negative externalities can be detected. Moreover, the effect is transitory, vanishing after five years at the latest. As wind turbines are addressed at avoiding negative externalities of local pollutant and global greenhouse gas emissions, they fulfil an important role in the de-carbonization of electricity systems world-wide. Comparing the imposed spatially and temporally limited externalities with the avoided externalities from emissions, the positive impact of wind turbines is by several magnitudes higher than the negative.
Keywords: C23; Q42; Q51; R20; 330; life satisfaction; social acceptance; wind power; wind turbines; renewables; externalities; SOEP; GIS; spatial analysis